Catastrophic out-of-pocket payments related to non-communicable disease multimorbidity and associated factors, evidence from a public referral hospital in Addis Ababa Ethiopia - Mizan Habtemichael; Meseret Molla; Berhan Tassew (BMC, 2024)
Abstract Background In low and middle-income countries (LMICs), non-communicable diseases (NCDs) are on the rise and have become a significant cause of mortality. Unfortunately, accessing affordable healthcare services can prove to be challenging for individuals who are unable to bear the expenses out of their pockets. For NCDs, the treatment costs are already high, and being multimorbid further amplifies the economic burden on patients and their families. The present study seeks to bridge the gap in knowledge regarding the financial risks that come with NCD multimorbidity. It accomplishes this by examining the catastrophic out-of-pocket (OOP) expenditure levels and the factors that contribute to it at Tikur Anbesa Specialized Hospital, Addis Ababa, Ethiopia. Methods A facility-based cross-sectional study was conducted at Tikur Anbesa Specialized Hospital between May 18 and July 22, 2020 and 392 multimorbid patients participated. The study participants were selected from the hospital's four NCD clinics using systematic random sampling. Patients' direct medical and non-medical out-of-pocket (OOP) expenditures were recorded, and the catastrophic OOP health expenditure for NCD care was estimated using various thresholds as cutoff points (5%, 10%, 15%, 20%, 25%, and 40% of both total household consumption expenditure and non-food expenditure). The collected data was entered into Epi Data version 3.1 and analyzed using STATA V 14. Descriptive statistics were utilized to present the study's findings, while logistic regression was used to examine the associations between variables. Results A study was conducted on a sample of 392 patients who exhibited a range of socio-demographic and economic backgrounds. The annual out-of-pocket spending for the treatment of non-communicable disease multimorbidity was found to be $499.7 (95% CI: $440.9, $558.6) per patient. The majority of these expenses were allocated towards medical costs such as medication, diagnosis, and hospital beds. It was found that as the threshold for spending increased from 5 to 40% of total household consumption expenditure, the percentage of households facing catastrophic health expenditures (CHE) decreased from 77.55 to 10.46%. Similarly, the proportion of CHE as a percentage of non-food household expenditure decreased from 91.84 to 28.32% as the threshold increased from 5 to 40%. The study also revealed that patients who traveled to Addis Ababa for healthcare services (AOR = 7.45, 95% CI: 3.41-16.27), who were not enrolled in an insurance scheme (AOR = 4.97, 95% CI: 2.37, 10.4), who had more non-communicable diseases (AOR = 2.05, 95% CI: 1.40, 3.01), or who had more outpatient visits (AOR = 1.46, 95%CI: 1.31, 1.63) had a higher likelihood of incurring catastrophic out-of-pocket health expenditures at the 40% threshold. Conclusion and recommendation This study has revealed that patients with multiple non-communicable diseases (NCDs) frequently face substantial out-of-pocket health expenditures (CHE) due to both medical and non-medical costs. Various factors, including absence from an insurance scheme, medical follow-ups necessitating travel to Addis Ababa, multiple NCDs and outpatient visits, and utilization of both public and private facilities, increase the likelihood of incurring CHE. To mitigate the incidence of CHE for individuals with NCD multimorbidity, an integrated NCD care service delivery approach, access to affordable medications and diagnostic services in public facilities, expanded insurance coverage, and fee waiver or service exemption systems should be explored.